Diagnostic and Management Ruptur Artery Radialis and Ulnaris Sinistra et causa Vascular Trauma : A Case Report - Okthara Sebayang, Abed Nego; Ibnu, Syahroni (Journal of Indonesia Vascular Access, 2023)
Background: Vascular trauma is a life-threatening injury caused by a stab wound, blunt, or iatrogenic wound that damages a blood vessel. Vascular trauma can involve arteries and veins. Vascular trauma requires diagnosis and action fast handling to avoid fatal consequences in the form of amputation. This case report will discuss vascular trauma to the radial and ulnar arteries due to work accidents. Case Description: A 19-year-old patient came with his colleague from the Emergency Department with the chief complaint of bleeding in his left hand. The patient experienced this while working on repairing electrical pipes an hour ago. The incident began when the electric cable fell from the power pole, and then the car grabbed the power cable so that it wrapped around the patient's left hand, injuring the patient's hand and bleeding. The supporting examination was an X-ray of the upper extremity. Although the impression on the radiological examination was that the radial and ulnar bones looked good, there were soft tissue defects in the dorsal-lateral of the distal antebrachial. However, on laboratory examination, blood was within normal limits. The treatment included vascular exploration surgery, vein autograft, harvesting of vena saphena Magna for vascular reconstruction, skin graft, and debridement. During treatment, the cruris Sinistra is given light therapy to repair damaged vascularisation. Conclusion: Vascular trauma is an injury caused by a stab wound, blunt object, or iatrogenic wound that damages a blood vessel.  In this case, ruptured artery radialis and ulnaris sinistra et cause trauma was found. Therefore, the treatment was to do vascular exploration surgery, vein autograft, harvesting of vena saphena magna for vascular reconstruction, and debridement.